Some Applications of Soft \(\partial\)-Closed Sets in Soft Closure Spaces - Saleh, S.; Flaih, Laith R.; Jasim, Khalid Fadhil (Communications in Mathematics and Applications, 2023)
This study aims to present some applications of the notion of soft \(\partial\)-closed sets in soft closure spaces, which not only generalizes classical soft closed sets but also establishes a connection with soft \(g\)-closed sets. We discuss their basic characterizations of these sets and examine their implications in soft closure spaces. Furthermore, we apply these sets to introduce the notion of \(S\partial\)-continuous and \(S\partial\)-closed maps and present their various properties with some supported examples. Moreover, we propose two separation properties, which utilize the notion of \(S\partial\)-closed sets and explore their characteristics.